TRAITS KEPRIBADIAN â€œTHE BIG FIVEâ€ DAN MUSICAL PERFORMANCE ANXIETY (MPA) PADA MUSISI - IRMA ROSALINDA; MICHELLE NEIVI ARTISSY (Journal of Research and Measurement in Psychology, 2016)
This study was conducted to determine the effect of personality traits of musical performance anxiety among musicians. As well as to find out which personality trait has the most effect of musical performance anxiety. This is a quantitative study with psychological scale. Researcher adapt the scale of performance anxiety inventory for musicians (PerfAIM) revised edition from Barbeau (2017) and adopt the big five inventory (BFI) scale from Ramdhani (2012). The item reliability for MPA are (0,97), openness (0,97), conscientiousness (0,95), extraversion (0,93), agreeableness (0,85), and neuroticism (0,88). Respondents of this study are 87 musicians. Hypothesis tested using regression analysis. The results shown that neuroticism has the higher effect of MPA which is 31,9%. And the effect is positive.